Neuropsychiatric profile in tuberous sclerosis complex patients with epilepsy - Osman, Mahmoud Fawzi; Hadid, Faisal; ben Omran, Tawfeg; Aden, Munira; Al-Maadid, Fatima; Altaraqji, Sondos; Mohamed, Khalid; Benini, Ruba (Frontiers in Pediatrics, 2025)
Background: Tuberous sclerosis complex (TSC) is an autosomal dominant disorder characterized by mutations in the TSC1 or TSC2 genes, leading to dysregulation of the mTOR pathway and multisystemic manifestations. Epilepsy is a common neurologic feature of TSC, frequently accompanied by neuropsychiatric comorbidities. Understanding the relationship between epilepsy severity, TSC-associated neuropsychiatric disorders (TAND), and cognitive outcomes is crucial for optimizing patient care. Methods: A retrospective study was conducted at a pediatric tertiary care hospital in Qatar, involving 38 TSC patients (20 female, 18 male) aged 1 to 18 years, diagnosed between October 2018 and March 2020. Epilepsy severity was assessed using the Early Childhood Epilepsy Severity Scale (E-Chess), and TAND was evaluated using the TAND checklist. Genetic analysis was performed for all patients, and statistical analyses were used to explore correlations between epilepsy severity, TAND, and cognitive outcomes. Results: The majority (82%) of TSC patients had epilepsy, with a mean onset age of 9.2 months. Uncontrolled seizures were associated with higher rates of intellectual disability and more pronounced TAND manifestations compared to controlled seizures. Autism spectrum disorder (ASD) was reported in 42% of the cohort, with significant correlations found between epilepsy severity and ASD-related domains on the TAND checklist. Intellectual disability was prevalent (67.6%), with variability attributed to genetic background and early severe neurological presentations. Discussion: This study reinforces the link between epilepsy severity and neuropsychiatric comorbidities in TSC, confirming earlier findings. Significant correlations were observed between epilepsy severity and ASD-related domains, and the high prevalence of intellectual disability in TSC patients was highlighted. However, the relationship between ASD, TSC, and epilepsy remains complex and requires further investigation. Despite advances in treatment options, including mTOR inhibitors and newer antiepileptic drugs, unmet needs remain in the comprehensive care of TSC patients. Conclusion: This study sheds light on the intricate interactions between epilepsy severity, neuropsychiatric manifestations, and cognitive outcomes in TSC patients. Further research is required to clarify the mechanisms underlying these associations and to develop targeted interventions for improving the quality of life for individuals with TSC and epilepsy.